Is running less skilled in triathletes than runners matched for running training history? - Chapman, A. R.; Vicenzino, B.; Blanch, P.; Hodges, P. W. (Medicine & Science in Sports & Exercise, 2008)
Purpose: Cycling muscle recruitment is less skilled in elite triathletes than in cyclists matched for cycling training history. This finding suggests that the multidiscipline training undertaken by triathletes interferes with adaptation of the neuromuscular system to cycling training in triathletes. The purpose of this study was to determine if similar interference with adaptation of the neuromuscular system would be evident during running in elite triathletes.